Interventions for Type 2 Diabetes reduction among older people living with HIV in Harare - Nongiwe L. Mhlanga; Thinavhuyo R. Netangaheni (South African Family Practice)
Background: Interventions for Type 2 Diabetes reduction among older people aged more than 50 years living with HIV (PLWH) are pertinent as they face excess risks amid a growing population of ageing PLWH.